Reviews of Teachers’ Characters in Students’ Autobiography - Sabardila, Atiqa; Markhamah, Markhamah; Pratiwi, Dini Restiyanti (Bina Nusantara University, 2020)
This research aimed to describe reviews of teachers’ characters found in students’ autobiography. This research belonged in the field of Indonesian Language Education, and the data were in the form of students’ autobiography, written in Indonesian. A descriptive-qualitative approach was utilized to observe the attitude, behavior, or perception of autobiographers about their teachers’ characters in the past. The source triangulation was used to verify the validity of the data. The data were analyzed through a comparative method using referential and marker reading techniques, in addition to the focused-group discussion. The results of this research show that the teachers’ characters portrayed in students’ autobiography includes: (1) positive characters: responsible, patient, caring, easy to understand, fair, making students smart, inspiring creativity; and (2) negative characters: fierce/yelling, scary in anger, hard to understand, flirty. From the results, it can be concluded that students’ autobiography evidently helps measure the quality of teachers’ characters, and negative characters reduce the learning process’s effectiveness.